THE GENEALOGY OF PEDAGOGY AS A SCIENTIFIC DISCOURSE IN LIGHT OF DISCIPLINE AND PUNISH – TOWARDS A PARADOX OF PEDAGOGICAL PHILOSOPHY - Krystyna Rybińska (Studia Humanistyczne AGH, 2016)
The aim of this article is to outline the philosophical genealogy of pedagogical discourse based on Michel Foucault’s Discipline and Punish (1977). The undertaken line of inquiry posits this reflection in light of the presupposed question about the core of pedagogical discourse since although in the course of the continuous academic debate stemming from Foucault’s writings many insightful works have emerged with regard to the critical analysis of the educational system and the inner logic underlying the functioning mode of the schools, and although the critical approach appears to be fundamental in the contemporary humanities, the very discourse seems to face an inter-conceptual resistance, which results in the fact that ‘with some hesitations and some dissent, contemporary critical traditions continue a nineteenth-century view of social redemption through schooling’ (Popkiewitz and Brennan 1998). In the article I put forward the possibility that the seemingly unresolvable theoretical resistance residing in the very essence of pedagogy as a scientific discourse, once reexamined in fact veils an inverted conception of pedagogical philosophy as the core of Foucault’s stance.